Modeling and simulation of direct contact membrane distillation system integrated with a photovoltaic thermal for electricity and freshwater production - Maqbool, Faisal; Soomro, Mujeeb Iqbal; Kumar, Laveet; Harijan, Khanji (Frontiers in Energy Research, 2024)
Energy drives the growth, transformation, and economic development of every nation. The vitality of human existence and progress hinges on the accessibility of both energy and water resources. As freshwater resources are diminishing, therefore, desalination needs have increased. In solar membrane distillation systems, the key challenge is maintaining the intake water temperature in the membrane distillation system with fluctuating solar radiation intensity which affects the distillate water quantity and quality. The objective of this study is to enhance and optimize a mathematical model for analyzing a cutting-edge solar-integrated PV/T-DCMD system. In this innovative integration, the direct contact membrane distillation intake water temperature is derived from the photovoltaic thermal output. The integration of direct contact membrane distillation with photovoltaic thermal systems represents a cost-effective and technologically advantageous concept. As the water temperature increases, there is a notable improvement in the evaporation efficiency of PV/T-DCMD systems, with an increase from 35.08% to 42.01%. Additionally, there is a reduction in specific thermal energy consumption, decreasing from 1,192 to 1,386 kWh/m3 as a consequence of the elevated feed water temperature.